Integrasi Konstitusional Kewenangan Judicial Review Mahkamah Konstitusi dan Mahkamah Agung - Maruarar Siahaan (The Constitutional Court of the Republic of Indonesia, 2020)
The separation of judicial review authority of the rules and regulation between the Supreme Court and the Constitutional Court raises many questions, what is the reason for the Reform of the 1945 Constitution to make this separation. The results of the study state that in countries that adopt the civil law system submit all judicial review authority to the MK, so that the separation of testing or judicial review that separates between the law that is the authority of the MK, and the testing of legislation under the law becomes the authority MA, is considered an awkward thing. Implications of the MK’s decision to test the legal norms of the 1945 Constitution, the scope of which may be horizontal to the same norms in the law, and vertically down to the rule of law as the implementation of the law that has been tested and stated to have no binding legal force. Conceptually the judicial review of the legislation should be under one roof. The burden of handling matters in the Supreme Court, can be a sufficient basis that the handling of judicial review under one roof system by the Constitutional Court, requires new interpretation or amendment to the 1945 Constitution, However, the conception will be difficult to realize except with the amendment of the 1945 Constitution because the divided judicial review authority is explicitly regulated in the 1945 Constitution. This will change if the MK’s decision with “courage” can give a new interpretation of the constitution, or through application of inherent/implied power jurisdiction of judicial constitutional review ”, then the granting and regulation of separate authorities made explicitly and expressively verbis in Article 24A and 24C, can be realized without demanding amendment to the 1945 Constitution concerning Article 24A paragraph (1) and Article 24C paragraph (1) of the 1945 Constitution.